Knowledge gaps in bleeding disorders: Results from an objective structured oral examination in internal medicine residency training. (15th March 2022) - Khalife, Roy; Tinmouth, Alan; Duffett, Lisa; Halman, Samantha
Abstract: Background: Empirical evidence for physicians' knowledge gaps in bleeding disorders is limited to self‐reported surveys, yet often cited as a leading cause of diagnostic and management delays. Objectives: Our aim was to assess internal medicine (IM) residents' competence, based on their training level, in evaluating a patient with a bleeding disorder, and knowledge gaps in their clinical approach. Methods: Content experts developed patient case presenting with abnormal bleeding, bruising, and an isolated prolonged PTT. We administered the hemostasis case as part of an objective structured clinical examination (OSCE). We performed a descriptive analysis. One‐way anova was conducted to compare the effect of training level on performance. Item difficulty level for the hemostasis case was also determined. Results: Sixty‐seven IM residents participated in the OSCE. The hemostasis case had the highest failure rate at 41.8% with a mean score for the station of 57.96% (SD 13.04). Senior residents scored significantly higher than junior residents on this case ( F (2, 64) = 4.604, p = .014, η p 2  = 0.126). The item difficulty analysis demonstrated challenges in in eliciting a history of bleeding provoked by challenges, examining the bleeding site, interpreting the mixing study, requesting appropriate follow‐up tests, making the diagnosis and providing acute management for a bleeding patient. Only 49.3% of residents requested a hematology consultation. Conclusions: We demonstrated important knowledge gaps in IM residents' approach to the bleeding patient. Innovative strategies for hemostasis education should be a priority to address physician‐related factors in the diagnostic and management delays of patients with bleeding disorders.